Emerging Evidence for Platelets as Immune and Inflammatory Effector Cells - Rondina, Matthew T.; Garraud, Olivier (Frontiers in Immunology, 2014)
While traditionally recognized for their roles in hemostatic pathways, emerging evidence demonstrates that platelets have previously unrecognized, dynamic roles that span the immune continuum. These newly-recognized platelet functions, including the secretion of immune mediators, interactions with endothelial cells, monocytes, and neutrophils, toll-like receptor (TLR) mediated responses, and induction of neutrophil extracellular trap (NET) formation, bridge thrombotic and inflammatory pathways and contribute to host defense mechanisms against invading pathogens. In this focused review, we highlight several of these emerging aspects of platelet biology and their implications in clinical infectious syndromes.